2016
DOI: 10.1002/prca.201600081
|View full text |Cite
|
Sign up to set email alerts
|

A detailed proteomic profiling of plasma membrane from zebrafish brain

Abstract: Zebrafish (Danio rerio) is a well-established model organism in developmental biology and disease modeling. In recent years, an increasing amount of studies used zebrafish to analyze the genetic changes underlying various neurological disorders. The brain plasma membrane proteome represents the major subsets of signaling proteins and promising drug targets, but is often understudied due to traditional experimental difficulties including problems with solubility, detergent removal, or low abundance. Here, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Taking into account this broad spectrum of Bbs functions as well as our current results elaborating the role of Bbs, such as reduction in dendritic spine density along with aberrant synaptic IGF receptor signalling and altered neurotransmitter receptor levels (NMDA and AMPA), we hypothesised that Bbs proteins may play a vital role in neuronal synapses. Re-evaluation of our earlier mass spectrometric analyses of synaptosomal [33,34] and crude synaptosomal fractions [35] of the rat cortex, dorsal striatum, and DG revealed the presence of Bbs1, Bbs2, Bbs4, Bbs5, Bbs7, and Bbs10 proteins (S1 Table).…”
Section: Resultsmentioning
confidence: 95%
“…Taking into account this broad spectrum of Bbs functions as well as our current results elaborating the role of Bbs, such as reduction in dendritic spine density along with aberrant synaptic IGF receptor signalling and altered neurotransmitter receptor levels (NMDA and AMPA), we hypothesised that Bbs proteins may play a vital role in neuronal synapses. Re-evaluation of our earlier mass spectrometric analyses of synaptosomal [33,34] and crude synaptosomal fractions [35] of the rat cortex, dorsal striatum, and DG revealed the presence of Bbs1, Bbs2, Bbs4, Bbs5, Bbs7, and Bbs10 proteins (S1 Table).…”
Section: Resultsmentioning
confidence: 95%
“…The pooled sample was separated by reversed-phase liquid chromatography (RP-LC) at high pH as previously described ( Gilar et al, 2005 ) resulting in 25 fractions. The peptide fractions were analyzed by liquid chromatography-tandem mass spectrometry (LC–MS/MS) with two technical replicates per sample using the LC separation procedure described previously ( Smidak et al, 2016 ). MS analysis was performed by the Thermo Scientific TM Q Exactive TM Plus Orbitrap mass spectrometer (Thermo Scientific) in positive ion mode with full-scan MS in the range of m/z 375–1400 at the resolution of 35,000 (at m/z 200).…”
Section: Methodsmentioning
confidence: 99%
“…In zebrafish brain, multiple RNA isoforms of the ryanodine-sensitive Ca 2+ channel (Ryr) have been identified (Darbandi and Franck, 2009;Holland et al, 2017;Tse et al, 2018), but the relative protein products have been partially analyzed (Wu et al, 2011). Zebrafish Purkinje cells express the IP3-sensitive Ca 2+ channel (ITPR1) in the cell body, the axon, the dendritic shaft, and the spines (Koulen et al, 2000), and adult zebrafish brain proteomic studies have identified Casq2 protein in total homogenates (Nolte et al, 2014;Smidak et al, 2016), but cell-type expression and localization remain to be elucidated. Based on current proteomic and transcriptomic studies, it is evident that multiple isoforms of Ca 2+ store components are expressed in adult zebrafish brain so that the latter is a suitable model to identify neuronal Ca 2+ stores in different cells and compartments.…”
Section: Neuronal Er Ca 2+ Binding Proteinsmentioning
confidence: 99%